Carbon Metabolic Pathways in Phototrophic Bacteria and Their Broader Evolutionary Implications - Tang, Kuo-Hsiang; Tang, Yinjie J.; Blankenship, Robert E. (Frontiers in Microbiology, 2011)
Photosynthesis is the biological process that converts solar energy to biomass, bio-products and biofuel. It is the only major natural solar energy storage mechanism on Earth. To satisfy the increased demand for sustainable energy sources and identify the mechanism of photosynthetic carbon assimilation, which is one of the bottlenecks in photosynthesis, it is essential to understand the process of solar energy storage and associated carbon metabolism in photosynthetic organisms. Researchers have employed physiological studies, microbiological chemistry, enzyme assays, genome sequencing, transcriptomics, and 13C-based metabolomics/fluxomics to investigate central carbon metabolism and enzymes that operate in phototrophs. In this report, we review diverse CO2 assimilation pathways, acetate assimilation, carbohydrate catabolism, the TCA cycle and some key and/or unconventional enzymes in central carbon metabolism of phototrophic microorganisms. We also discuss the reducing equivalent flow during photoautotrophic and photoheterotrophic growth, evolutionary links in the central carbon metabolic network, and correlations between photosynthetic and non-photosynthetic organisms. Considering the metabolic versatility in these fascinating and diverse photosynthetic bacteria, many essential questions in their central carbon metabolism still remain to be addressed.